ANALISIS PENGEMBANGAN WILAYAH KOTA SEMARANG BERBASIS POTENSI UNGGULAN DAERAH - Hendrianto Sundaro; Agus Sarwo Edy Sudrajat (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2019)
This research reveals about the regional development of the Semarang City based on superior potential. The analytical tool used in this study is the Location Quotion analysis, Klassen Typology analysis and Shift Share analysis. The results showed that there were 11 potential economic sectors in the Semarang City which were the (leading) base sector.From the results of the LQ analysis obtained information that the base sector with the highest LQ value is the Information and Communication sector with an LQ value of 2.815 while the base sector with the lowest LQ value (1.04) is the supply, accommodation and food and beverage sector. From the results of Typology Klassen's analysis it was identified that there were only 1 sector included in the category of advanced and fast-growing sectors (quadrant I), ten sectors included in the category of advanced but distressed sectors (Quadrant III) and 6 Sectors included in the category of relatively lagging sectors (Quadrant IV ). While from the calculation of Shift Share analysis, it is known that the regional growth component (N) and the industrial mix component (M) are positive while the competitiveness component (C) all sectors are negative except for the Communication and Information sector.From the results of the analysis conducted, the direction of regional development policy in the city of Semarang must be focused on the identified base sector so that the Semarang City can develop in accordance with its superior potential.